Homoeopathy in Covid 19 Sequelae: A Case of Telogen Effluvium (Advancements in Homeopathic Research, 2024)
Hair loss is one of the most prevalent complaints in  patients shortly after being infected with Covid-19,  reported more commonly in women. The most  likely cause could be either the pathogenetic aspects  or psychiatric complications of Covid-19, which  can lead to the appearance or aggravation of hair  loss. Homoeopathy has a vital role to play in such  areas; where no specific therapeutic intervention is  available in modern medicine especially when the  disease is stress induced. Since Homoeopathy is the  only healing science that takes care of the patient  as a whole; the root cause, the physical and mental  state of the patient along with the disease symptoms  which individualizes the patient from one another  are the basis of accurate and effective homoeopathic  prescription. Following the cardinal principles,  significant improvement and recovery was seen in  such cases with homoeopathic remedies.
Keywords: Hair fall; Post Covid; Telogen effluvium; Homeopathy; Acid phosphoricum; Sepia